Producing Quality Bokashi Compost, Development of Certified Chili Seedlings, and Processing Flavored Milk - Sudjatmiko, Sigit; Ganefianti, Dwi Wahyuni; Sulistyowati, Endang (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
The program aimed to produce high-quality bokashi compost, develop certified chilli seeds, and process cow's milk into flavored milk products. The results demonstrated that combining raw materials from the farmyard with dairy farm yard produced bokashi compost with favorable nutrient content: total nitrogen at 1.3%, phosphorus at 0.99%, potassium at 1.3%, organic carbon at 26.12%, and a C/N ratio of 17.18 qualified the standards of SNI 19-7030-200. Additionally, a comparison of 4 chilli hybrids with a combination revealed that the hybrid combination between UNIB C H63 x UNIB C H43 in the one plot achieved greater plant height and canopy area. However, although differences in yield components were not statistically significant, the single cropping of hybrids UNIB C H13 and UNIB C H53 significantly improved the resistance to yellow leaf curl disease. Lastly, the flavoured milk development resulted in a high-quality product with a fat content of 3.91%, protein at 3.30%, lactose at 4.96%, and a specific gravity of 1.032. Overall, the program successfully met its objectives, producing quality compost, promising chilli hybrids, and nutritious flavored milk.